Dukungan Keluarga dan Peran Pengawas Minum Obat dengan Kepatuhan Minum Obat pada Penderita TB Paru - Yogi Ravo Aprindo; Mila Triana Sari; Marnila Yesni; Daryanto Daryanto (Jurnal Akademika Baiturrahim Jambi, 2023)
Tuberculosis (TB) is a bacterial infection caused by Mycobacterium Tuberculosis. The most deadly infectious illness on the globe is still pulmonary tuberculosis. Southeast Asia accounts for up to 58% of all TB cases. India, Indonesia, and China have the greatest number of TB cases in the globe, accounting for 23%, 10%, and 10% of global incidence, respectively. The overall goal of this study is to examine the association between family support and the function of medication supervisors in pulmonary tuberculosis patients at the Putri Ayu Health Center in Jambi City. This is a cross-sectional quantitative study. The investigation was conducted in the operating area of the Putri Ayu Health Center in Jambi City in August 2022. This study included all active tuberculosis patients at the Putri Ayu Health Center, a total of 66 individuals. The study's sample size was 60 people (after deducting 6 respondents of the initial survey). Total sampling is the sampling technique used. The analysis performed is both univariate and bivariate. The chi square test was applied, with a meaningfulness threshold of 95% (alpha = 0.05). The study revealed a link between family support (p-value: 0.021) and the role of supervisors taking medications (p-value: 0.010) and adherence to taking drugs in pulmonary TB patients at the Putri Ayu Health Center in Jambi City. It is expected that the Puskesmas Putri Ayu Jambi City would also educate families and emphasise the need of family support for active Tb patients' rehabilitation and develop a PMO optimization program to prevent drop out.